IN VITRO PROPAGATION OF KAEMPFERIA MARGINATA CAREY EX ROSCOE, A NATIVE PLANT SPECIES TO THAILAND - P. Saensouk; N. Muangsan; S. Saensouk; P. Sirinajun (Journal of Animal and Plant Sciences, 2016)
Kaempferia marginata Carey ex Roscoe is used in northeastern Thailand as a vegetable. The conventional method for propagation of K. marginata Carey ex Roscoe is through the use of rhizomes, but this has low proliferation rates. The tissue culture technique provides an alternative method of propagation for mass production. Callus induction as well as shoot and root formation was studied when culturing microshoots of K. marginata Carey ex Roscoe on Murashige and Skoog (MS) medium supplemented with (thidiazuron) TDZ,  (6-benzyl adenine) BA plus TDZ and BA plus (6-furfuryl amino purine) Kinetin for 6 weeks. The highest percentage of callus induction was 90% when the microshoot was cultured on MS medium supplemented with 2 mg L-1 BA plus 1.5, 3 or 4 mg L-1 TDZ. The best result for shoot multiplication was 4.90 shoots/explant achieved on MS medium added with 2 mg L-1 BA and 1 mg L-1 TDZ. The maximum number of roots were obtained on MS medium without plant growth regulators. Rooted shoots were transplanted into burned rice husk and sand (1:1 w/w) in a greenhouse and their survival was 100%.
Keywords: In vitro; Propagation; Microshoot; Callus induction; Kaempferia marginata Carey ex Roscoe